Decomposing Deontic Modality: Evidence from Korean. (3rd December 2019) - Chung, WooJin
Abstract: Korean deontic modal expressions inform about the composition of modality which is not evident from languages that express modal concepts via an auxiliary or a verb. They are expressed in terms of a conditional and an evaluative predicate: permission and obligation respectively translate to 'even if φ , good' and 'only if φ , good', where φ is the prejacent. John-un maykcwu-lul masi-eto toy-n-ta John-top beer-acc drink-even.if good-pres-decl 'John may drink beer.' John-un maykcwu-lul masi-eya toy-n-ta John-top beer-acc drink-only.if good-pres-decl 'John must/should/ought to drink beer.' Their transparent morphosyntax lets us probe deeper into the interior of deontic modal concepts. I propose that Korean deontic modal expressions do not set up the domain of quantification in which the prejacent is evaluated. Instead, they assess the goodness of the prejacent and its alternatives, all else being equal. I allude to the possibility that English obligation also involves similar reasoning by offering a counterfactual-based account of the Professor Procrastinate puzzle. On the other hand, Korean permission gives rise to a specific interpretation of strong permission, conveying that the truth or falsity of the prejacent does not affect the deontic status. I additionally point out that Korean has a separate copula-based construction for expressing modal possibility, which hints that there are in fact two types of permission in natural language.